Semaji - Black Community Resource Centre (BCRC) (2019)

Semaji - Black Community Resource Centre (BCRC) (2019)

Semaji - Black Community Resource Centre (BCRC) (2019)

Selected Papers from the 2018 Conference on Community Education and Development: Perspectives on English-Speaking Blacks and Minorities - Black Community Resource Centre (BCRC) (Community Education and Development: perspectives on English-Speaking Blacks and Other Minorities, 2018)
The Black Community Resource Centre (BCRC) is a growing, resource-based organization that strengthens community capacity by providing professional support to organizations and individuals in need. The Centre is committed to helping visible minority youth rekindle their dreams, and achieve their full potential.We take a comprehensive approach to meet the needs of English-speaking youth. By referring to the “Holistic Project” approach through our community service, we recognize that youth have many needs (e.g., socio-cultural, educational, and economic, etc.) that must be addressed in order for youth to achieve their greatest potential in our society.
Keywords: Official Language Minority Community (OLMC)

Semaji - Black Community Resource Centre (BCRC) (2018)

Semaji - Black Community Resource Centre (BCRC) (2018)

Semaji - Black Community Resource Centre (BCRC) (2018)

Semaji - Black Community Resource Centre (BCRC) (2018)

Semaji - Black Community Resource Centre (BCRC) (2018)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2017)

Semaji - Black Community Resource Centre (BCRC) (2016)

Semaji - Black Community Resource Centre (BCRC) (2016)

Semaji - Black Community Resource Centre (BCRC) (2016)

Semaji - Black Community Resource Centre (BCRC) (2015)

Semaji - Black Community Resource Centre (BCRC) (2015)

Semaji - Black Community Resource Centre (BCRC) (2015)

Semaji - Black Community Resource Centre (BCRC) (2015)

The Black Community Resource Guide 2010/2011 - Black Community Resource Centre (BCRC) (2011)

Semaji - Black Community Resource Centre (BCRC) (2010)

Semaji - Black Community Resource Centre (BCRC) (2010)

Semaji - Black Community Resource Centre (BCRC) (2010)